Occurrence of soft and hard corals at Igang Bay and Villa Corazon, Nueva Valencia Guimaras: A Comparative Survey - Magramo, Melchor; Esmaña, Mary Mar; Flores, June Raymond Peter; Terunez, Marlon (JPAIR Multidisciplinary Research, 2010)
In the waters off Nueva Valencia, Guimaras, Philippines, researchers compared the health of coral communities at Igang Bay and Villa Corazon. This study examined differences in soft and hard coral cover and colony abundance between the sites, along with variations in the overall coral health. Additionally, the team evaluated the physico-chemical properties of the water to understand potential environmental influences on these coral reef ecosystems.